A case of congenital bronchial atresia patient with subclinical infection who underwent lung resection. (2020) - Murata, Saori; Oguri, Tomoyo; Sasada, Shinji; Tsuchiya, Yumi; Ishioka, Kota; Takahashi, Saeko; Kuriyama, Shoji; Kaji, Masahiro; Seki, Reishi; Hirose, Shigemichi; Nakamura, Morio
Abstract: Congenital bronchial atresia, CBA, is rare and has often asymptomatic benign condition. The CBA condition usually arose during the formation of bronchi, but the CBA patients are able to live well into adulthood. This case highlights a potential surgical intervention for a CBA patient with subclinical infection. A 55-year-old Japanese male had abnormal findings on his chest X-ray at an annual health check-up in March 2018. His chest computed tomography (CT) revealed bronchial stenosis and infiltrative shadow in the right inferior lobe. He was referred to our hospital for further investigation and was diagnosed CBA after a variety of examinations including bronchoscopy. His dilated bronchi were filled with mucus, the end of one of the bronchi had obstructive pneumonia, and subclinical infection in the CBA lesion was suspected. Also, the result of bronchoscopy disclosed intrabronchial infection with Gram-positive bacteria so we performed lobectomy onto the lower lobe. Although no protocol had been established, a surgical intervention would be necessary for this case.